Predicting peatland groundwater table and soil moisture dynamics affected by drainage level - Bambang Widiarso; Slamet Minardi; Komariah Komariah; Tino Orciny Chandra; Mohamed Abdesalam Elmahdi; Masateru Senge (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2020)
Excessive drainage of peatlands can cause subsidence and irreversible drying; therefore, it is necessary to predict groundwater levels in peatlands to ensure adequate water for crops and control excessive water loss simultaneously. This study aimed to predict the peatland groundwater level and soil moisture affected by drainage. This research was conducted in a peatland located in Rasau Jaya Umum, Kubu Raya Regency, West Kalimantan Province, Indonesia from February to December 2016. Three treatments of drainage setting were established with maize cropping: without drainage (P0) and drainage channel with water level maintained at depths of 30 cm (P1) and 60 cm (P2) from the soil surface. The results indicated that a polynomial regression model is a good approach to predicting groundwater table level and soil moisture in peatlands, with R2 values ranging 0.71-0.96 and 0.65-0.93, respectively. For agricultural purposes, maintaining the water level at 30 cm from the soil surface in the drainage channel appears to be the ideal level as adequate soil moisture is provided for annual cash crops and drying is prevented simultaneously.